Kajian Eksperimen Pengaruh Variasi Perubahan Sudut Kincir terhadap Kinerja Paddle Wheel Aerator - Mustaghfirin, Anis; Novianarenti, Eky; Abid Al Fatih, Muhammad; Nugroho, Priyambodo Nur Ardi; Sasmita Aji Pambudi, Dwi; Arum Wulandari, Dyah (P3M Politeknik Negeri Cilacap, 2023)
The main problem discussed in this study is the effort to improve the quality of shrimp pond water, especially the low dissolved oxygen levels by modifying the angle of the aerator wheel. The results showed that dissolved oxygen (DO) levels were very important in shrimp pond culture and that the paddle wheel aerator was a useful tool in intensive aquaculture systems because it could produce DO as needed. The study used a model designed using Solidworks software and tested at a scale of 1:10 with 3 variations of angles (15°, 35°, and 55°) at each wheel angle. The test results show that the angle variation affects the rotational speed and DO production, with the highest rotational speed and DO production achieved at an angle variation of 55°. However, the best parameters for the aerator were found at a variation of the wheel angle of 35° and a rotational speed of 300 rpm, because it produced the highest dissolved oxygen with relatively low power.